Levodopa Added to Stroke Rehabilitation: The ESTREL Randomized Clinical Trial - Engelter, Stefan T; Kaufmann, Josefin E; Zietz, Annaelle; Luft, Andreas R; Polymeris, Alexandros; Altersberger, Valerian L; Wiesner, Karin; Wiegert, Martina; Held, Jeremia P O; Rottenberger, Yannik; Schwarz, Anne; Medlin, Friedrich; et al. (JAMA : the journal of the American Medical Association, 2025)
Levodopa enhances dopaminergic signaling and may stimulate neuroplasticity, which could potentially enhance motor recovery after stroke. Levodopa is used in stroke rehabilitation despite mixed evidence for its effectiveness. To determine whether levodopa compared with placebo, administered in addition to standardized rehabilitation based on active task-oriented training, is associated with enhanced motor recovery in patients with acute stroke. A double-blind, placebo-controlled randomized clinical trial at 13 stroke units and centers and 11 collaborating rehabilitation centers in Switzerland. Between June 14, 2019 (first patient, first visit), and August 27, 2024 (last patient, last visit), 610 patients with acute ischemic or hemorrhagic stroke with clinically meaningful hemiparesis (ie, a total score of ≥3 points on the following National Institutes of Health Stroke Scale items: motor arm, motor leg, or limb ataxia) were randomized 1:1 to receive levodopa or placebo. Statistical analyses were conducted from November 2024 to August 2025. Patients received levodopa/carbidopa (100 mg/25 mg; n = 307) or placebo (n = 303) 3 times daily for 39 days, alongside standardized rehabilitation therapy based on active task-oriented training. The primary outcome was the adjusted mean between-group difference in the Fugl-Meyer Assessment (FMA) total score (range, 0-100 points; fewer points indicate worse motor function; 6-point difference considered patient-relevant) at 3 months. Among the 610 participants (median [IQR] age, 73 [64-82] years; 252 [41.3%] female; median baseline FMA total score, 34 [14-54]), 28 participants died by 3 months, leaving 582 (95.4%) participants eligible for the primary analysis. At 3 months, the median (IQR) FMA total score was 68 (42-85) points in the levodopa group and 64 (44-83) points in the placebo group. The mean difference in the FMA total score between the levodopa and placebo groups was -0.90 points (95% CI, -3.78 to 1.98; P = .54). There were 126 serious adverse events in the levodopa group and 129 in the placebo group; the most common was infection (levodopa, n = 55; placebo, n = 44). In this randomized clinical trial, among patients receiving inpatient rehabilitation for acute stroke, levodopa added to standardized rehabilitation did not significantly improve motor function at 3 months compared with placebo plus standardized rehabilitation. These results do not support the use of levodopa as an adjunct to rehabilitation therapy for enhancing motor recovery after acute stroke. ClinicalTrials.gov Identifier: NCT03735901.